Au-ni-w composite film modified copper-based material, preparation and method for solid phase welding thereof

CN117845293BActive Publication Date: 2026-10-09GUANGDONG SONGSHAN POLYTECHNIC COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311615366.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2026-10-09
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

传统的金属-金属热压焊接受到器件表面形貌的限制,温度高达300-400℃

Benefits of technology

[0022] This invention achieves optimal welding morphology for the material's hierarchical structure by adjusting the type of crystallization modifier and deposition time. An amorphous Ni-W alloy is obtained by adjusting the ratio of W and Ni atoms. This allows for the fabrication of a Ni-W composite film modifying the copper-based material, including a copper-based micro/nano hierarchical structure and an Au-modified layer. The Au-Ni-W composite film maintains a sharp conical array structure within the copper-based micro/nano hierarchical structure. As a barrier layer between the copper base and the solder, the Au-Ni-W composite film prevents the interdiffusion between copper and tin, exhibits corrosion resistance at high temperatures, and delays interfacial reactions. Combined with ultrasonic-assisted solid-state welding, the copper-based micro/nano hierarchical structure is completely embedded into the solder, improving oxidation and void issues in insert welding. Furthermore, the solid-state welding technology is completed transiently at room temperature, reducing internal thermal deformation of the chip, simplifying complex processes, reducing energy consumption, and aligning with the trend of green packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117845293B_ABST
    Figure CN117845293B_ABST
Patent Text Reader

Abstract

The application discloses an Au-Ni-W composite film modified copper-based material and a preparation and solid phase welding method thereof, and belongs to the technical field of material welding, which comprises the following steps: placing pretreated substrates into a sulfuric acid solution for 15-20 s, then placing the substrates into a palladium chloride solution for 60-80 s, and finally placing the substrates into an electroplating solution for 10-30 min to obtain a copper-based micro-nano hierarchical structure; placing the copper-based micro-nano hierarchical structure wrapped substrates into an alloy plating solution, and obtaining a Ni-W composite film with a thickness of 150-220 nm after electroplating; and placing the Ni-W composite film wrapped substrates into a KAu(CN)2 solution, and obtaining the Au-Ni-W composite film modified copper-based material after electroplating. The optimal welding morphology of the material hierarchical structure is obtained by adjusting the type of crystallization modifier and the deposition time, the amorphous Ni-W alloy is obtained by adjusting the proportion of W and Ni atoms, the Au-Ni-W composite film modified copper-based micro-nano hierarchical structure keeps a sharp conical array structure, and the oxidation and hole problems in the plug-in welding are improved by cooperating with the solid phase welding under the ultrasonic assistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials welding technology, specifically relating to a copper-based material modified with an Au-Ni-W composite thin film, its preparation, and a method for solid-state welding. Background Technology

[0002] 3D integrated packaging transmits signals in the shortest vertical path, enabling systems with higher density, higher performance, smaller form factor, and lower power consumption. Due to the consideration of high interconnect density, stack-up bonding technology is considered a key technology for 3D integrated packaging. Traditional metal-to-metal thermocompression bonding is limited by the surface morphology of the device, with temperatures reaching 300-400℃. Because of issues such as high-energy irradiation and post-bonding thermal stress control, this high-temperature process is rarely used.

[0003] In high-density packaging, the integrity of the interface between the solder and the substrate plays a crucial role in the reliability of the solder joint. Therefore, the intermetallic compound formed at the solder interface is of decisive significance. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0005] In view of the problems existing in the above and / or prior art, the present invention is proposed.

[0006] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing copper-based materials modified with Au-Ni-W composite thin films.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: the pretreated copper substrate is immersed in sulfuric acid solution for 15-20 seconds, then activated in palladium chloride solution for 60-80 seconds, and finally deposited in electroplating solution for 10-30 minutes to obtain a copper substrate with copper-based micro-nano hierarchical structure.

[0008] A copper substrate with a copper-based micro / nano hierarchical structure was placed in an alloy plating bath, and the plating bath temperature was 60–80℃, and the current density was 4A / dm³. 2 Under these conditions, electroplating for 150–220 s yields a Ni-W composite film with a thickness of 150–220 nm.

[0009] The Ni-W composite film encapsulating the substrate was placed in a KAu(CN)2 solution and subjected to a pulse frequency of 100Hz, a duty cycle of 1:6–9, and a current density of 0.3A / dm³ at 60–80℃.2 After electroplating for 15–30 seconds, a copper-based material modified with an Au-Ni-W composite thin film is obtained.

[0010] The main salts in the alloy plating solution are nickel chloride and sodium tungstate.

[0011] In a preferred embodiment of the method for preparing the Au-Ni-W composite thin film modified copper-based material according to the present invention, the pretreatment involves immersing the copper substrate in an acetone solution and applying an A / dm² solution. 2 Degrease at a current density of 10–30 min.

[0012] In a preferred embodiment of the method for preparing the Au-Ni-W composite thin film modified copper-based material according to the present invention, the concentration of the palladium chloride solution is 0.1-0.3 g / L.

[0013] In a preferred embodiment of the method for preparing the Au-Ni-W composite thin film modified copper-based material according to the present invention, the electroplating solution comprises, by mass percentage: 10%–15% copper sulfate, 0.5%–2% nickel sulfate, 20%–25% boric acid, 20%–25% trisodium citrate, 25%–30% sodium hypophosphite, 1%–4% polyethylene glycol, and 7%–12% sodium hydroxide.

[0014] In a preferred embodiment of the method for preparing the Au-Ni-W composite thin film modified copper-based material according to the present invention, the alloy plating solution comprises, by mass percentage, 30%–40% citric acid, 15%–25% HEDP, 8%–40% sodium tungstate, and 3%–15% nickel chloride.

[0015] In a preferred embodiment of the method for preparing the copper-based material modified with Au-Ni-W composite thin film according to the present invention, the concentration of the KAu(CN)2 solution is 0.4-0.8 g / L.

[0016] Another objective of this invention is to overcome the shortcomings of the prior art and provide a copper-based material modified with an Au-Ni-W composite thin film.

[0017] Another objective of this invention is to overcome the shortcomings of the prior art and provide a solid-state welding method for copper-based materials modified with Au-Ni-W composite thin films.

[0018] To solve the above-mentioned technical problems, the present invention provides the following technical solution: welding of copper-based materials modified with Au-Ni-W composite thin films to SAC305 solder under ultrasonic assistance and solid-state conditions, and aging treatment of the welded samples.

[0019] As a preferred embodiment of the solid-state welding method for Au-Ni-W composite thin film modified copper-based materials according to the present invention, the welding pressure is 18-25 MPa, the welding time is 2-6 s, and the ultrasonic treatment time is 2-6 s.

[0020] As a preferred embodiment of the solid-state welding method for copper-based materials modified with Au-Ni-W composite thin films according to the present invention, the aging treatment temperature is 160℃-200℃ and the aging treatment time is 30-90min.

[0021] Beneficial effects of this invention:

[0022] This invention achieves optimal welding morphology for the material's hierarchical structure by adjusting the type of crystallization modifier and deposition time. An amorphous Ni-W alloy is obtained by adjusting the ratio of W and Ni atoms. This allows for the fabrication of a Ni-W composite film modifying the copper-based material, including a copper-based micro / nano hierarchical structure and an Au-modified layer. The Au-Ni-W composite film maintains a sharp conical array structure within the copper-based micro / nano hierarchical structure. As a barrier layer between the copper base and the solder, the Au-Ni-W composite film prevents the interdiffusion between copper and tin, exhibits corrosion resistance at high temperatures, and delays interfacial reactions. Combined with ultrasonic-assisted solid-state welding, the copper-based micro / nano hierarchical structure is completely embedded into the solder, improving oxidation and void issues in insert welding. Furthermore, the solid-state welding technology is completed transiently at room temperature, reducing internal thermal deformation of the chip, simplifying complex processes, reducing energy consumption, and aligning with the trend of green packaging. Attached Figure Description

[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:

[0024] Figure 1 This is a SEM image of the layered structure of the Au-Ni-W composite thin film modified copper-based material prepared in Example 1 of the present invention.

[0025] Figure 2 This is a SEM image of the layered structure of the Au-Ni-W composite thin film modified copper-based material obtained in Example 2 of the present invention.

[0026] Figure 3 This is a SEM image of the layered structure of the Au-Ni-W composite thin film modified copper-based material prepared in Example 3 of the present invention.

[0027] Figure 4This is a SEM image of the layered structure of the Au-Ni-W composite thin film modified copper-based material obtained in Example 4 of the present invention.

[0028] Figure 5 This is a schematic diagram of the welding process.

[0029] Figure 6 This is a SEM image of the welding interface in Embodiment 5 of the present invention.

[0030] Figure 7 This is a SEM image of the welding interface of Comparative Example 1 of the present invention.

[0031] Figure 8 This is a SEM image of the welding interface of Comparative Example 2 of the present invention.

[0032] Figure 9 This is a SEM image of the welding interface of Comparative Example 3 of the present invention. Detailed Implementation

[0033] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0034] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0036] The substrate used in this invention is lead frame material C194, with dimensions of 80mm*60mm;

[0037] The solder used in this invention is SAC305.

[0038] Unless otherwise specified, all raw materials used in this invention are commercially available.

[0039] Example 1

[0040] This embodiment provides a method for preparing Au-Ni-W composite thin film modified copper-based materials, specifically as follows:

[0041] 1) Prepare the electroplating solution according to the following components: CuSO4·5H2O (10g / L), NiSO4·5H2O (1g / L), H3BO3 (20g / L), Na3C6H5O7 (20g / L), NaH2PO2 (25g / L), PEG 10000 (2g / L), NaOH (8g / L);

[0042] 2) Prepare the alloy plating solution according to the following components: Na3C6H5O7·2H2O (75g / L), HEDP (50wt.%) (45g / L), Na2WO4·2H2O (65g / L), NiCl2·6H2O (25g / L), pH=5.5;

[0043] 3) Place the substrate at 6A / dm 2 The oil was removed under a current density of 20 min, then soaked in a sulfuric acid solution with a volume content of 20% for 20 s, then activated in a 0.2 g / L palladium chloride solution for 60 s, and finally deposited in an electroplating solution for 15 min to obtain a copper-based micro-nano hierarchical structure.

[0044] 4) Immerse the substrate in the alloy plating solution at a temperature of 65℃ and a current density of 4A / dm³. 2 Under these conditions, electroplating for 180 seconds yielded a Ni-W composite film.

[0045] 5) A pulsed DC power supply is used, with a pulse frequency of 100Hz, a duty cycle of 1:9, and a current density of 0.3A / dm³. 2 Under the condition of KAu(CN)2 concentration of 0.6 g / L, an Au layer was obtained by electroplating for 20 s, resulting in a copper-based material modified with Au-Ni-W composite film.

[0046] Example 2

[0047] The difference between this embodiment and Embodiment 1 is that the composition of the electroplating solution is adjusted, specifically:

[0048] 1) Prepare the electroplating solution according to the following components: CuSO4·5H2O (10g / L), NiSO4·5H2O (1g / L), H3BO3 (20g / L), Na3C6H5O7 (20g / L), NaH2PO2 (25g / L), PEG 2000 (2g / L), NaOH (8g / L);

[0049] 2) Prepare the alloy plating solution according to the following components: Na3C6H5O7·2H2O (75g / L), HEDP (50wt.%) (45g / L), Na2WO4·2H2O (65g / L), NiCl2·6H2O (25g / L), pH=5.5;

[0050] 3) Place the substrate at 6A / dm 2 The oil was removed under a current density of 20 min, then soaked in a sulfuric acid solution with a volume content of 20% for 20 s, then activated in a 0.2 g / L palladium chloride solution for 60 s, and finally deposited in an electroplating solution for 15 min to obtain a copper-based micro-nano hierarchical structure.

[0051] 4) Immerse the substrate in the alloy plating solution at a temperature of 65℃ and a current density of 4A / dm³. 2 Under these conditions, electroplating for 180 seconds yielded a Ni-W composite film.

[0052] 5) A pulsed DC power supply is used, with a pulse frequency of 100Hz, a duty cycle of 1:9, and a current density of 0.3A / dm³. 2 Under the condition of KAu(CN)2 concentration of 0.6 g / L, an Au layer was obtained by electroplating for 20 s, resulting in a copper-based material modified with Au-Ni-W composite film.

[0053] Example 3

[0054] The difference between this embodiment and Embodiment 1 is that the composition of the electroplating solution is adjusted, specifically:

[0055] 1) Prepare the electroplating solution according to the following components: CuSO4·5H2O (10g / L), NiSO4·5H2O (1g / L), H3BO3 (20g / L), Na3C6H5O7 (20g / L), NaH2PO2 (25g / L), PEG10000 (2g / L), NaOH (8g / L);

[0056] 2) Prepare the alloy plating solution according to the following components: Na3C6H5O7·2H2O (75g / L), HEDP (50wt.%) (45g / L), Na2WO4·2H2O (65g / L), NiCl2·6H2O (25g / L), pH=5.5;

[0057] 3) Place the substrate at 6A / dm 2 The oil was removed under a current density of 20 min, then soaked in a 20% sulfuric acid solution for 20 s, then activated in a 0.2 g / L palladium chloride solution for 60 s, and finally deposited in an electroplating solution for 30 min to obtain a copper-based micro-nano hierarchical structure.

[0058] 4) Immerse the substrate in the alloy plating solution at a temperature of 65℃ and a current density of 4A / dm³. 2 Under these conditions, electroplating for 180 seconds yielded a Ni-W composite film.

[0059] 5) A pulsed DC power supply is used, with a pulse frequency of 100Hz, a duty cycle of 1:9, and a current density of 0.3A / dm³. 2Under the condition of KAu(CN)2 concentration of 0.6 g / L, an Au layer was obtained by electroplating for 20 s, resulting in a copper-based material modified with Au-Ni-W composite film.

[0060] Example 4

[0061] The difference between this embodiment and Embodiment 1 is that the composition of the electroplating solution is adjusted, specifically:

[0062] 1) Prepare the electroplating solution according to the following components: CuSO4·5H2O (10g / L), NiSO4·5H2O (1g / L), H3BO3 (20g / L), Na3C6H5O7 (20g / L), NaH2PO2 (25g / L), PEG10000 (2g / L), NaOH (8g / L);

[0063] 2) Prepare the alloy plating solution according to the following components: Na3C6H5O7·2H2O (75g / L), HEDP (50wt.%) (45g / L), Na2WO4·2H2O (30g / L), NiCl2·6H2O (60g / L), pH=5.5;

[0064] 3) Place the substrate at 6A / dm 2 The oil was removed under a current density of 20 min, then soaked in a sulfuric acid solution with a volume content of 20% for 20 s, then activated in a 0.2 g / L palladium chloride solution for 60 s, and finally deposited in an electroplating solution for 15 min to obtain a copper-based micro-nano hierarchical structure.

[0065] 4) Immerse the substrate in the alloy plating solution at a temperature of 65℃ and a current density of 4A / dm³. 2 Under these conditions, electroplating for 180 seconds yielded a Ni-W composite film.

[0066] 5) A pulsed DC power supply is used, with a pulse frequency of 100Hz, a duty cycle of 1:9, and a current density of 0.3A / dm³. 2 Under the condition of KAu(CN)2 concentration of 0.6 g / L, an Au layer was obtained by electroplating for 20 s, resulting in a copper-based material modified with Au-Ni-W composite film.

[0067] The copper-based materials modified with Au-Ni-W composite films prepared in Examples 1 to 4 were analyzed respectively, and the results are shown in Table 1.

[0068] Table 1

[0069]

[0070] According to Table 1 and Appendix Figure 1 ~Attached Figure 4It can be seen that the type of crystallization modifier and deposition time affect the morphology of the copper-based micro / nano hierarchical structure and the coating thickness. The microstructure of the deposit prepared using PEG 2000 exhibits a star-shaped pyramidal structure with an average height of 1-1.5 μm and an average root diameter of approximately 0.5-1 μm. The deposit prepared using PEG 10000 exhibits a serrated, uniform conical structure with an average cone height of approximately 3-5 μm and an average root diameter of approximately 1 μm. The formation of these unique structures is attributed to the role of PEG in controlling the growth rate of different copper crystal faces. PEG as a single additive is based on the concept of uneven adsorption distribution. Higher molecular weight PEG has a better ability to inhibit nucleation and crystal growth (especially root diameter), thereby controlling the growth rate of these crystal faces through adsorption and desorption. Higher molecular weight PEG tends to promote crystal growth rather than nucleation. When the molecular weight of PEG increases from 2000 to 10000, the density of the microstructure decreases, but the size increases. Appropriate microstructure size contributes to the mechanical interlocking effect in subsequent insert welding.

[0071] When the mass fraction of W exceeds 44%, W atoms approach saturation within the Ni atomic lattice, no longer forming a solid solution structure. The long-range ordered arrangement of atoms changes, and the Ni atomic lattice undergoes lattice distortion due to the intrusion of W atoms. This lattice distortion increases with increasing W content, resulting in a transformation of the coating structure from an initial crystalline to an amorphous state. The amorphous coating structure exhibits high hardness, smoothness, and high density, lacking defects such as grain boundaries, dislocations, and twins. It also possesses advantages in wear resistance and oxidation resistance at high temperatures. The modified copper-based structure retains its needle-like cone structure, which is beneficial for subsequent insert welding. The corrosion current density is directly proportional to the corrosion rate. After modification with Au-Ni-W alloy, the corrosion current density of the Cu-based micro / nano hierarchical structure increases from 10.73 μA / cm². 2 Reduced to 0.95 μA / cm 2 The corrosion rate of the sample decreased significantly, and the corrosion resistance of the Au / Ni-W alloy was enhanced after modification with a Cu-based micro / nano hierarchical structure.

[0072] Example 5

[0073] See attached document Figure 5 This embodiment provides a solid-state welding method for Au-Ni-W composite thin film modified copper-based materials, specifically as follows:

[0074] The copper-based material modified with Au-Ni-W composite film obtained in Example 1 was placed on the stage of a welding instrument as the substrate. SAC305 was used as the solder. The welding pressure was set to 10000gf, the welding time to 3s, and the ultrasonic vibration to 3s, respectively, to obtain the welded sample.

[0075] Example 6

[0076] This embodiment provides a solid-state welding method for Au-Ni-W composite thin film modified copper-based materials, specifically:

[0077] The Au-Ni-W composite thin film modified copper-based material prepared in Example 1 was placed on the stage of a welding instrument as the substrate. SAC305 was used as the solder. The welding pressure was set to 5000gf, 200000gf, the welding time was 3s, and the ultrasonic vibration was set for 3s to obtain the welded sample.

[0078] Example 7

[0079] This embodiment provides a solid-state welding method for Au-Ni-W composite thin film modified copper-based materials, specifically:

[0080] The Au-Ni-W composite thin film modified copper-based material prepared in Example 1 was placed on the stage of a welding instrument as the substrate. SAC305 was used as the solder, and the welding time was set to 1s, 3s, and 5s, the welding pressure was 10000gf, and the ultrasonic vibration was set to 3s to obtain the welded sample.

[0081] Example 8

[0082] This embodiment provides a solid-state welding method for Au-Ni-W composite thin film modified copper-based materials, specifically:

[0083] The Au-Ni-W composite film modified copper-based material prepared in Example 1 was placed on the stage of a welding instrument as the substrate. SAC305 was used as the solder. The ultrasonic vibration was set for 1s, 3s, and 5s, the welding time was 3s, and the welding pressure was 10000gf to obtain the welded sample.

[0084] The average shear strength of the welded interface obtained in Examples 5 to 8 is shown in Table 2.

[0085] Table 2

[0086]

[0087] Table 2 shows that the average shear strength of the weld interface is closely related to the welding pressure, welding time, and ultrasonic time. The average shear strength of the weld interface increases with increasing welding pressure. This is because with increasing welding pressure, the Ni-W composite film is pressed deeper into the solder, resulting in a larger contact area with the solder. This allows for the replication of micro-nano details within the solder, creating a mechanical interlocking effect and significantly increasing the average shear strength of the weld interface. When the welding pressure is 5000 gf (10 MPa), the Au-Ni-W composite film is not fully inserted into the solder due to the relatively low pressure, resulting in numerous pores and gaps at the weld interface and a low average shear strength. When the welding pressure increases to 10000 gf (20 MPa), the Au-Ni-W composite film is essentially embedded in the solder, the pores at the weld interface are filled, and the average shear strength reaches 40.5 MPa. However, further increases in welding pressure have limited effect on the average shear strength of the weld interface.

[0088] As welding time increases, the average shear strength of the weld interface increases. This is because the increased welding time allows the solder sufficient time for plastic deformation and flow, enabling it to fill the recessed areas at the weld interface and form a weld interface with fewer or no defects. When the welding time is 1 second, the solder does not have enough time to fill the gaps, resulting in a low average shear strength. When the welding time is increased to 3 seconds, the solder completes the flow and gap-filling process under pressure, leading to a significant increase in the average shear strength of the weld interface. Further increasing the welding time to 5 seconds does not significantly reduce the porosity of the weld interface, nor does it significantly increase the average shear strength. To obtain a higher quality weld interface, other methods must be combined, such as subsequent heat treatment and ultrasonic treatment.

[0089] Appropriate ultrasonic treatment time has a significant impact on the quality of the weld interface. The transverse vibration and heat energy provided by ultrasonic treatment promote the flow and filling of solder and the interdiffusion of atoms. When the ultrasonic treatment time is 1 to 3 seconds, under the conditions of transverse friction and heat energy, the flow and atomic diffusion performance of solder are improved, the pores at the weld interface disappear, and a defect-free weld interface is obtained, resulting in excellent welding effect. When the ultrasonic treatment time reaches 5 seconds, the transverse vibration actually aggravates the generation and rapid propagation of cracks at the weld interface, which greatly reduces the average shear strength of the weld interface.

[0090] Comparative Example 1

[0091] Comparative Example 1 is based on Example 1. The difference between Comparative Example 1 and Example 1 is that the composition of the electroplating solution is adjusted, specifically:

[0092] 1) Prepare an electroplating solution with the following components: CuSO4·5H2O (30g / L), NiSO4·5H2O (3g / L), H3BO3 (20g / L), Na3C6H5O7 (20g / L), NaH2PO2 (25g / L), PEG 10000 (0.5g / L), NaOH (8g / L);

[0093] 2) Prepare the alloy plating solution according to the following components: Na3C6H5O7·2H2O (75g / L), HEDP (50wt.%) (45g / L), Na2WO4·2H2O (65g / L), NiCl2·6H2O (25g / L), pH=5.5;

[0094] 3) Place the substrate at 6A / dm 2 The oil was removed under a current density of 20 min, then soaked in a sulfuric acid solution with a volume content of 20% for 20 s, then activated in a 0.2 g / L palladium chloride solution for 60 s, and finally deposited in an electroplating solution for 15 min to obtain a copper-based micro-nano hierarchical structure.

[0095] 4) Immerse the substrate in the alloy plating solution at a temperature of 65℃ and a current density of 4A / dm³. 2 Under these conditions, electroplating for 180 seconds yielded a Ni-W composite film.

[0096] 5) A pulsed DC power supply is used, with a pulse frequency of 100Hz, a duty cycle of 1:9, and a current density of 0.3A / dm³. 2 Under the condition of KAu(CN)2 concentration of 0.6 g / L, an Au layer was obtained by electroplating for 20 s, resulting in a copper-based material modified with Au-Ni-W composite film.

[0097] Comparative Example 2

[0098] Comparative Example 2 is based on Example 1. The difference between Comparative Example 2 and Example 1 is that the composition of the electroplating solution is adjusted, specifically:

[0099] 1) Prepare the electroplating solution according to the following components: CuSO4·5H2O (10g / L), NiSO4·5H2O (1g / L), H3BO3 (20g / L), Na3C6H5O7 (20g / L), NaH2PO2 (25g / L), PEG 10000 (2g / L), NaOH (8g / L);

[0100] 2) Prepare the alloy plating solution according to the following composition: Na3C6H5O7·2H2O (75g / L), HEDP (50wt.%)

[0101] (45g / L), Na2WO4·2H2O (30g / L), NiCl2·6H2O (60g / L), pH=5.5;

[0102] 3) Place the substrate at 6A / dm 2 The oil was removed under a current density of 20 min, then soaked in a sulfuric acid solution with a volume content of 20% for 20 s, then activated in a 0.2 g / L palladium chloride solution for 60 s, and finally deposited in an electroplating solution for 15 min to obtain a copper-based micro-nano hierarchical structure.

[0103] 4) Immerse the substrate in the alloy plating solution at a temperature of 65℃ and a current density of 4A / dm³. 2 Under these conditions, electroplating for 180 seconds yielded a Ni-W composite film.

[0104] 5) A pulsed DC power supply is used, with a pulse frequency of 100Hz, a duty cycle of 1:9, and a current density of 0.3A / dm³. 2 Under the condition of KAu(CN)2 concentration of 0.6 g / L, an Au layer was obtained by electroplating for 20 s, resulting in a copper-based material modified with Au / Ni-W composite film.

[0105] Comparative Example 3

[0106] Comparative Example 3 is based on Example 1. The difference between Comparative Example 3 and Example 1 is that the composition of the electroplating solution is adjusted, specifically:

[0107] 1) Prepare the electroplating solution according to the following components: CuSO4·5H2O (10g / L), NiSO4·5H2O (1g / L), H3BO3 (20g / L), Na3C6H5O7 (20g / L), NaH2PO2 (25g / L), PEG 10000 (2g / L), NaOH (8g / L);

[0108] 2) Prepare the alloy plating solution according to the following components: Na3C6H5O7·2H2O (75g / L), HEDP (50wt.%) (45g / L), Na2WO4·2H2O (65g / L), NiCl2·6H2O (25g / L), pH=5.5;

[0109] 3) Place the substrate at 6A / dm 2 The oil was removed under a current density of 20 min, then soaked in a sulfuric acid solution with a volume content of 20% for 20 s, then activated in a 0.2 g / L palladium chloride solution for 60 s, and finally deposited in an electroplating solution for 15 min to obtain a copper-based micro-nano hierarchical structure.

[0110] 4) Immerse the substrate in the alloy plating solution at a temperature of 65℃ and a current density of 4A / dm³. 2Under these conditions, electroplating for 180 seconds yielded a Ni-W composite film.

[0111] 5) A pulsed DC power supply is used, with a pulse frequency of 100Hz, a duty cycle of 1:9, and a current density of 0.3A / dm³. 2 Under the condition of KAu(CN)2 concentration of 0.6 g / L, an Au layer was obtained by electroplating for 20 s, resulting in a copper-based material modified with Au / Ni-W composite film.

[0112] The copper-based materials modified with Au-Ni-W composite films prepared in Comparative Examples 1 to 3 were analyzed, and the results are shown in Table 3.

[0113] Table 3

[0114]

[0115] The copper-based materials modified with Au / Ni-W composite films prepared in Comparative Examples 1 and 2 were placed on the stage of a welding instrument as substrates. SAC305 was used as solder, and the welding pressure was set to 10000 gf, the welding time to 3 s, and the ultrasonic vibration to 3 s, respectively, to obtain the welded samples. The copper-based materials modified with Au / Ni-W composite films prepared in Comparative Example 3 were placed on the stage of a welding instrument as substrates. SAC305 was used as solder, and the welding pressure was set to 5000 gf, the welding time to 5 s, and the ultrasonic vibration to 5 s, respectively, to obtain the welded samples.

[0116] The average shear strength of the welded interface obtained in Comparative Examples 1 to 3 is shown in Table 4.

[0117] Table 4

[0118]

[0119] According to Table 3, Table 4 and Appendix Figure 6 ~Attached Figure 9It can be seen that the average shear strength of the weld interface is closely related to the morphology of the copper-based material micro / nano hierarchical structure modification layer and key welding parameters. When the W content is higher than 44%, the Ni-W alloy is amorphous. During ultrasonic welding, a dense oxide film easily forms due to the high temperature. This oxide film is relatively stable and difficult to remove. The oxide film does not react with the solder ball, hindering the diffusion of the micro / nano hierarchical structure and tin, and thus failing to form a strong bond. After Au film modification, the oxidation of the Au-Ni-W alloy layer is prevented. Moreover, Au has a high activation energy and reacts rapidly with tin to form intermetallic compounds, obtaining a stable bonding interface. A new phase with inconsistent contrast was observed at the diffusion interface of the Ni-W alloy layer, exhibiting a "bright layer" structure. This is a W-enriched layer with a thickness of approximately 100 nm. The W-enriched layer, known as the "bright layer," exists throughout the diffusion interface. A new phase is formed on the solder side above the "bright layer," exhibiting a different contrast than the enriched layer. This phase is a Cu-Ni-Sn intermetallic compound. No new phase appears on the side of the copper-based micro / nano hierarchical structure below the "bright layer." It is speculated that the presence of W inhibits the further diffusion of Sn, thus blocking the growth of the Cu-Sn intermetallic compound. The weld interface exhibits high shear strength.

[0120] In Comparative Example 1, the copper-based micro / nano hierarchical structure obtained in this invention exhibits inconspicuous nanoscale protrusions. The Au / Ni-W composite thin film copper-based material tends to form a flat layer structure, making it difficult for the three layers to form interlocking during welding. The weld interface has almost no mechanical interlocking effect, resulting in low average shear strength. In Comparative Example 2, the copper-based micro / nano hierarchical structure shows significant surface variations, with fine protrusions on the surface. These protrusions are Ni-W alloy modification layer grains, with a W content of less than 44%, forming a Ni-W alloy crystalline structure. W atoms form a solid solution within the Ni atomic lattice. This crystalline coating structure has an uneven surface, and the Ni-W alloy modification layer grains are relatively coarse, with a grain size of approximately 100 nm, resulting in a low nanoscale hardness value. The coarse grain size of the Ni-W alloy and the uneven coating structure have a certain impact on the average shear strength of the weld interface. The copper-based micro / nano hierarchical structure was found to be almost completely inserted into the solder. A few tiny pores were present near the bottom of the micro / nano structure at the welding interface. The average shear strength of the welding interface was approximately 30.4 MPa, which is still some distance from that of traditional commercial solders. In Comparative Example 3, the welding pressure was too low, and the copper-based micro / nano hierarchical structure was not completely inserted into the solder, resulting in a large seam at the welding interface. Increasing the welding time and ultrasonic treatment time did not eliminate the pores at the welding interface; instead, the transverse vibration of the ultrasound promoted the generation and rapid propagation of transverse cracks at the welding interface, causing a significant decrease in the average shear strength of the welding interface.

[0121] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a copper-based material modified with an Au-Ni-W composite thin film, characterized in that: include, The pretreated copper substrate was immersed in sulfuric acid solution for 15-20 seconds, then activated in palladium chloride solution for 60-80 seconds, and finally deposited in electroplating solution for 10-30 minutes to obtain a copper substrate with copper-based micro-nano hierarchical structure. The pretreatment involves immersing the copper substrate in an acetone solution and applying a current density of 4-8 A / dm² to remove oil for 10-30 minutes. The electroplating solution comprises, by mass percentage: 10%–15% copper sulfate, 0.5%–2% nickel sulfate, 20%–25% boric acid, 20%–25% trisodium citrate, 25%–30% sodium hypophosphite, 1%–4% polyethylene glycol, and 7%–12% sodium hydroxide; the sum of the percentages of all components in the electroplating solution is 100%. A copper substrate with a copper-based micro / nano hierarchical structure was placed in an alloy plating bath, and the plating was performed at a temperature of 60-80℃ and a current density of 4 A / dm². 2 Under these conditions, electroplating for 150-220 s yields a Ni-W composite film with a thickness of 150-220 nm. The Ni-W composite film encapsulating the substrate was placed in a KAu(CN)2 solution and subjected to a pulse frequency of 100 Hz, a duty cycle of 1:6~9, and a current density of 0.3 A / dm³ at 60~80 ℃. 2 Electroplating for 15-30 seconds yields a copper-based material modified with an Au-Ni-W composite thin film. The main salts in the alloy plating solution are nickel chloride and sodium tungstate; The alloy plating solution comprises, by mass percentage, 30%~40% citric acid, 15%~25% HEDP, 8%~40% sodium tungstate, and 3%~15% nickel chloride; the sum of the percentages of each component in the alloy plating solution is 100%.

2. The method for preparing copper-based materials modified with Au-Ni-W composite thin films as described in claim 1, characterized in that: The sulfuric acid solution has a volume fraction of 20%, and the palladium chloride solution has a concentration of 0.1 ~ 0.3 g / L.

3. The method for preparing copper-based materials modified with Au-Ni-W composite thin films as described in claim 1, characterized in that: The concentration of the KAu(CN)2 solution is 0.4~0.8 g / L.

4. The copper-based material modified with Au-Ni-W composite thin film prepared by any one of the preparation methods described in claims 1 to 3.

5. The solid-state welding method for copper-based materials modified with Au-Ni-W composite thin films as described in claim 4, characterized in that: Welding of copper-based materials modified with Au-Ni-W composite films to SAC305 solder was performed under ultrasonic-assisted, solid-state conditions, and the welded samples were then subjected to aging treatment.

6. The solid-state welding method for copper-based materials modified with Au-Ni-W composite thin films as described in claim 5, characterized in that: The welding pressure is 18~25 MPa, the welding time is 2~6 s, and the ultrasonic treatment time is 2~6 s.

7. The solid-state welding method for copper-based materials modified with Au-Ni-W composite thin films as described in claim 5, characterized in that: The aging treatment temperature is 160℃-200℃, and the aging treatment time is 30~90 min.